2013
DOI: 10.1038/bjc.2012.586
|View full text |Cite
|
Sign up to set email alerts
|

Marine polyunsaturated fatty acids and cancer therapy

Abstract: Polyunsaturated fatty acids (PUFAs) derived from marine sources, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are widely consumed as supplements within the community. However, the use of marine PUFAs in a therapeutic context is also increasing in patients receiving treatment for a range of cancer types. On balance, the literature suggests that marine PUFAs have potential as an effective adjuvant to chemotherapy treatment, may have direct anticancer effects, and may help ameliorate some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 40 publications
0
97
0
1
Order By: Relevance
“…This hypothesis could explain the results obtained from the evaluation of the influence of oil fish (rich in EPA and DHA) on CRC [27]. EPA/DHA in doses of >1 g of EPA and >0.8 g of DHA are associated with positive clinical outcomes (in terms of quality of life) in cancer patients [28]. Results from the meta-analysis performed by Wu et al including 22 prospective cohorts and 19 case-control studies showed that fish consumption may reduce CRC risk by 12%.…”
Section: Relevance Of Fish As a Source Of Omega-3 Fatty Acidsmentioning
confidence: 93%
“…This hypothesis could explain the results obtained from the evaluation of the influence of oil fish (rich in EPA and DHA) on CRC [27]. EPA/DHA in doses of >1 g of EPA and >0.8 g of DHA are associated with positive clinical outcomes (in terms of quality of life) in cancer patients [28]. Results from the meta-analysis performed by Wu et al including 22 prospective cohorts and 19 case-control studies showed that fish consumption may reduce CRC risk by 12%.…”
Section: Relevance Of Fish As a Source Of Omega-3 Fatty Acidsmentioning
confidence: 93%
“…It has also been demonstrated that omega-3 FAs exert a range of anti-tumor effects, including inhibitory effects on angiogenic mediator production (5), the induction of apoptosis (6), inhibitory effects on tumor invasion and metastasis (7,8) and regulatory effects on signaling pathways (9). In particular, the anti-tumor effects of EPA and DHA have been observed in breast cancer, whereby higher intakes of these FAs are associated with a reduced risk of mortality (10,11). It has also been demonstrated that administration of DHA during anthracyclin-based chemotherapy against metastatic breast cancer improves clinical outcomes, suggesting that omega-3 FA may be an effective adjuvant in the treatment of cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified the development of cardiovascular disease and certain cancers with a higher dietary intake ratio of n-6 to n-3 PUFAs (Halberg, Cornelissen, & Singh, 2011;Isomaa et al, 2001;Vaughan, Hassing, & Lewandowski, 2013). In several countries, diets tend to be high calorie, with inadequate lipid profiles, high levels of saturated and n-6 PUFAs, and less than optimal levels of n-3 PUFAs.…”
Section: Introductionmentioning
confidence: 99%